2015
DOI: 10.1039/c5ob00544b
|View full text |Cite
|
Sign up to set email alerts
|

Titanium carbenoid-mediated cyclopropanation of allylic alcohols: selectivity and mechanism

Abstract: A new method for the chemo- and stereoselective conversion of allylic alcohols into the corresponding cyclopropane derivatives has been developed. The cyclopropanation reaction was carried out with an unprecedented titanium carbenoid generated in situ from Nugent's reagent, manganese and methylene diiodide. The reaction involving the participation of an allylic hydroxyl group, proceeded with conservation of the alkene geometry and in a high diastereomeric excess. The scope, limitations and mechanism of this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…However, when the reaction of 1 was quenched with pivaloyl, valeroyl, and benzoyl chlorides, the corresponding O ‐acylation products 44 – 46 (Entries 1–3, Table ) were obtained quantitatively, and again the corresponding cyclopropyl derivatives were not detected. These results confirm the key role of the solvent in the Ti III ‐mediated cyclopropanation …”
Section: Resultssupporting
confidence: 77%
“…However, when the reaction of 1 was quenched with pivaloyl, valeroyl, and benzoyl chlorides, the corresponding O ‐acylation products 44 – 46 (Entries 1–3, Table ) were obtained quantitatively, and again the corresponding cyclopropyl derivatives were not detected. These results confirm the key role of the solvent in the Ti III ‐mediated cyclopropanation …”
Section: Resultssupporting
confidence: 77%
“…Our results have shown that primary, secondary, tertiary, allylic and benzylic alcohols can be converted into their THF ethers at room temperature in good to excellent yield by the complex A , and quantitatively by the complex B . Our previous report on the titanium(III) mediated cyclopropanation7 showed that this would only proceed when THF was used as the solvent revealing the important role of the solvent in these reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism involves coupled cycles in which the Ti III species is regenerated at various stages by the excess Mn 0 and both a molecule of THF and another of the corresponding alcohol7,17 are coordinated in the half‐open structure D affording the E structure. In one of these (cycle 2, Scheme ), the Ti III species generates the dibromomethane radical from CHBr 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have reported that the titaniummediated cyclopropanation of geraniol by CH 2 I 2 may proceed without previous protection of the hydroxyl group. 39 Therefore, we expected that the presence of an unprotected hydroxyl group would be compatible with the use of n-BuLi in pentane in combination with a methylene source for alkene cyclopropanation. Consequently, in order to gain further insight into the chemoselectivity of the reaction, we explored the effect of different lithium carbenoids, using unprotected geraniol as a model substrate (Table 1).…”
Section: Resultsmentioning
confidence: 99%